Microstructural corrosion of aluminium alloys: a predictive finite element model based on corrosion–mimicking experiments. (14th February 2013) - Sorriano, Claire; Oltra, Roland; Zimmer, Alexandre; Vuillemin, Bruno; Vuillemin, Bruno; Borkowski, Celine
ABSTRACT The purpose of this study is to implement the basis of a finite element model (FEM) based on the resolution of the Nernst–Planck equation in order to progress in the predictive simulation of microstructural corrosion on aluminium alloys. Certain constituent intermetallic particles at the surface of aluminium alloys are considered as preferential sites for the initiation of structural corrosion resulting in localised trenching around the particles and the surrounding Al matrix. In this work, a modified scanning electrochemical microscope (SECM) experiment was used to induce such phenomena via a local alkalinization on 200 nm thick aluminium coatings, promoting their local dissolution in an aerated 0.1 M NaCl electrolyte. Using a 2D finite element modelling to simulate the SECM experiments, the role of the local alkalinization was validated and the calculated Al dissolution rate was found in agreement with the experimental evaluation. The same FEM model was then successfully applied to simulate the damage formed around a micrometric copper particle embedded in pure aluminium. Copyright © 2013 John Wiley & Sons, Ltd.